2017
DOI: 10.1371/journal.pone.0172797
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin and atorvastatin reduce the mechanical properties of tendon constructs in vitro and introduce catabolic changes in the gene expression pattern

Abstract: Treatment with lipid-lowering drugs, statins, is common all over the world. Lately, the occurrence of spontaneous tendon ruptures or tendinosis have suggested a negative influence of statins upon tendon tissue. But how statins might influence tendons is not clear. In the present study, we investigated the effect of statin treatment on mechanical strength, cell proliferation, collagen content and gene expression pattern in a tendon-like tissue made from human tenocytes in vitro. Human tendon fibroblasts were gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 30 publications
0
23
1
Order By: Relevance
“…These features were noted in all groups, including controls, and were not more prevalent in any specific group. In vitro studies have demonstrated changes in matrix production due to statin treatment 27 , but our findings did not support a notable change in proteoglycan content with any treatment condition. In this study, we found consistent and significant differences in weights of the animals in the CTL group versus those in the HC and HC+S groups.…”
Section: Discussioncontrasting
confidence: 99%
“…These features were noted in all groups, including controls, and were not more prevalent in any specific group. In vitro studies have demonstrated changes in matrix production due to statin treatment 27 , but our findings did not support a notable change in proteoglycan content with any treatment condition. In this study, we found consistent and significant differences in weights of the animals in the CTL group versus those in the HC and HC+S groups.…”
Section: Discussioncontrasting
confidence: 99%
“…Despite their positive effects, statins also have adverse effects on muscle, including myalgias, myositis, rhabdomyolysis, and myopathies [ 14 , 15 , 16 ]. Eliasson et al recently reported that simvastatin and atorvastatin have negative effects on tendons due to the decreased mechanical properties of tendon constructs and catabolic changes in the gene expression pattern [ 17 ]. These adverse effects mainly occur in the setting of high statin doses.…”
Section: Introductionmentioning
confidence: 99%
“…In keeping with this possibility, a number of laboratory studies have demonstrated a direct impairment of collagen metabolism in response to statin exposure, including reduced type I collagen levels and increased expression and activity of several matrix metalloproteinases. [ 7 , 8 , 9 ] However, the best evidence available to date comprises a propensity-score matched study of over 500,000 statin-users in the UK: in that study, statin use was not associated with an increased risk of Achilles tendon rupture. [ 10 ] In their discussion, the authors noted that their study could not exclude the possibility that statins might lead to milder tendon injury such as tendinopathy.…”
Section: Introductionmentioning
confidence: 99%